A dietary polyphenol resveratrol acts to provide neuroprotection in recurrent stroke models by regulating AMPK and SIRT1 signaling, thereby reducing energy requirements during ischemia. (3rd April 2016) - Wang, L.‐M.; Wang, Y.‐J.; Cui, M.; Luo, W.‐J.; Wang, X.‐J.; Barber, P.A.; Chen, Z.‐Y.
Abstract : The above article from European Journal of Neuroscience, published online on 5 March 2013 in Wiley Online Library(http://onlinelibrary.wiley.com/doi/10.1111/ejn.12162/full ), has been retracted by agreement between the Editors‐in‐Chief, Paul Bolam and John Foxe, the authors and John Wiley & Sons Ltd. The retraction has been agreed as Dr Phillip Barber has informed the publisher that he had seen neither the original data nor any version of the manuscript, and had not been involved in the work reported. A subsequent Institutional investigation found evidence of misconduct on the part of the submitting author. Reference Wang, L.‐M., Wang, Y.‐J., Cui, M., Luo, W.‐J., Wang, X.‐J., Barber, P.A. & Chen, Z.‐Y. (2013) A dietary polyphenol resveratrol acts to provide neuroprotection in recurrent stroke models by regulating AMPK and SIRT1 signaling, thereby reducing energy requirements during ischemia. Eur. J. Neurosci., 37, 1669–1681. doi:10.1111/ejn.12162